Biden’s Burden: Cleaning up Trump’s environmental mess - Cole, Daniel H. (The Opole Studies in Administration and Law, 2021)
Before the US can make progress on climate policy or environmental policy more generally, the new administration of President Joseph R. Biden must first undo the damage created by his predecessor in office, who dismantled existing US climate policy, pulled the US from the Paris Agreement, and sought to disable the Environmental Protection Agency (EPA) from regulating polluters. The courts blocked some of the Trump Administration’s more egregious anti-environmental protection policies for violating the 1946 Administrative Procedures Act and/or the express terms of an environmental protection statute (such as the Clean Air Act or Clean Water Act), but the Biden Administration still has a great deal of work to do. Already, Biden has announced that the US will rejoin the Paris Agreement as part of its plans not just to reinstate but to expand on climate policies adopted during the Obama Administration. This essay explains how the Biden Administration plans to achieve these climate policy goals, using mostly the very same administrative tools that the Trump Administration used to undo Obama era climate policies. Inter alia, advantages and disadvantages of pursuing policy goals administratively, rather than through legislative processes, will be addressed.